2018
DOI: 10.1002/chem.201804304
|View full text |Cite
|
Sign up to set email alerts
|

Does a Conjugation Site Affect Transport of Vitamin B12–Peptide Nucleic Acid Conjugates into Bacterial Cells?

Abstract: Gram‐negative bacteria develop specific systems for the uptake of scarce nutrients, including vitamin B12. These uptake pathways may be utilized for the delivery of biologically relevant molecules into cells. Indeed, it was recently reported that vitamin B12 transported an antisense peptide nucleic acid (PNA) into Escherichia coli and Salmonella Typhimurium cells. The present studies indicate that the conjugation site of PNA to vitamin B12 has an impact on PNA transport into bacterial cells. Toward this end, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Furthermore, we have shown that vitamin B 12 acts as a carrier of PNA to E. coli and Salmonella enterica subsp. enterica serovar Typhimurium [119,125]. These studies indicate that vitamin B 12 could be a good candidate for a PNA transporter into bacteria.…”
Section: Delivery Of Pna To Bacteriamentioning
confidence: 74%
“…Furthermore, we have shown that vitamin B 12 acts as a carrier of PNA to E. coli and Salmonella enterica subsp. enterica serovar Typhimurium [119,125]. These studies indicate that vitamin B 12 could be a good candidate for a PNA transporter into bacteria.…”
Section: Delivery Of Pna To Bacteriamentioning
confidence: 74%
“…The TBDTs can be also hijacked by colicins [5], bacteriophages [6], and sideromycins [7] to enter the bacterial cells. Recently, we have shown that vitamin B 12 delivers peptide nucleic acid and 2'O-methyl RNA oligomers into E. coli and S. Typhimurium cells [8][9][10][11]. Thus, vitamin B 12 may be used as a carrier of various oligonucleotides to bacterial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we investigated the ability of the natural noncationic carrier vitamin B 12 to transport PNA oligomers into E. coli cells. 20,26 Encouraged by the observation that conjugation of vitamin B 12 transports PNA to E. coli cells, we now tested the antibacterial potential of such conjugates using a PNA sequence with antibacterial properties, namely, the PNA aimed to target the mRNA transcript of an essential gene. Such PNA, targeting the expression of an essential protein, should inhibit bacterial growth provided that it is delivered to the cell interior and bound to the target at required concentrations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is not harmful for humans, cannot be overdosed, and does not induce resistance in bacteria. Moreover, vitamin B 12 can be chemically modified just in few steps with high synthetic efficacy; the conjugation procedure is simple and high yielding. , Furthermore, some derivatives of vitamin B 12 (e.g., derivatives of cobyric acid and cobinamide) are specifically recognized by bacteria, and not by mammalian cells, so they can be applied directly to bacterial cells. , Undeniably, the natural uptake properties of vitamin B 12 in different bacteria still need to be further researched; however, all the above should make vitamin B 12 , at least in principle, a better transporter of antisense PNAs in terms of further medical use.…”
Section: Resultsmentioning
confidence: 99%